EVALUASI PROGRAM KEGIATAN PROJEK PENGUATAN PROFIL PELAJAR PANCASILA (P5) FASE B DI SD NEGERI KALICACING 02 SALATIGA - Yuniar Utami, Tika; Tyas Asri Hardini, Agustina (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This study aims to evaluate the project program for strengthening the Pancasila student profile (P5) in the independent curriculum for class IV Phase B at Kalicacing 02 Salatiga State Elementary School. The type of research used is evaluation with the type of program evaluation using the CIPP model (Context, input, process, product). Data collection techniques were carried out by interview, observation, and document study. The data validation technique uses data triangulation by using data analysis techniques, namely data collection, data reduction, data presentation, and conclusion drawing. In the implementation of this research, the principal, teachers, students, and parents as research subjects. The results of the research on the context aspect are related to government regulations regarding the implementation of P5 in accordance with the applicable independent curriculum and regarding the letter of implementation of the P5 program made at SD Negeri Kalicacing 02 Salatiga. In the input aspect, which includes human resources, implementation funds, facilities and infrastructure, it is in accordance with what is needed, but improvement is still needed in several aspects. The process aspect includes preparation, implementation, supporting and inhibiting factors, and the effectiveness of the time available. And the results of research on the product aspect are that it can make students more creative and active because they can get fun learning outside the classroom. Keywords: CIPP, pancasila student profile program phase B, program evaluation